2021
DOI: 10.33166/aetic.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Brainwave Classification of Task Performed by Stroke Patients using ANN

Abstract: In this research, 14 stroke patient's brainwave activity with open eyes (OE) and close eyes (CE) sessions are used. This work aims to study and classify 2 activities that validate our data acquisition. The data set of each subject is used to classify the state of the subject during electroencephalogram (EEG) recording. For the classification model, the input signals are alpha, beta, theta, and delta bands. The classification algorithm used in this work is the Artificial Neural Network (ANN). The accuracy value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In conclusion, this study has shed light on the current landscape of learning style detection research while providing valuable insights into promising areas for future exploration. By continuing to address these research gaps and advancing methodological approaches, researchers can contribute to the ongoing growth and significance of learning style detection research, ultimately fostering more effective and personalized learning experiences for diverse learners (Narudin, Nasir and Fuad, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study has shed light on the current landscape of learning style detection research while providing valuable insights into promising areas for future exploration. By continuing to address these research gaps and advancing methodological approaches, researchers can contribute to the ongoing growth and significance of learning style detection research, ultimately fostering more effective and personalized learning experiences for diverse learners (Narudin, Nasir and Fuad, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…4). Reference [39] study classified two activities open eyes (OE) and close eyes (CE) sessions for 14 subjects having a stroke. The proposed methodology uses Artificial Neural Network (ANN) to train on input signals having EEG bands i.e., alpha, beta, theta, and delta, results obtained from the study suggested that ANN can be used to successfully classify stroke using brain activity.…”
Section: B Music Methodmentioning
confidence: 99%